Analysis of university entrants forum information content - Shilinh, Anna; Zhezhnych, Pavlo (Видавництво Львівської політехніки, 2013)
This article dwells upon the fact that in the result of transition to information society Web 2.0 became popular and developped in WWW extending into all life areas and human activity. Among one of the popular services Web 2.0 are educational web-community, studies of which nowadays are topical.
Keywords: Web 2.0; virtual educational community; webforum; information content